The effects of exercise-induced muscle damage on cycling time-trial performance - Burt, D. G.; Twist, C. (The Journal of Strength and Conditioning Research, 2011)
Previous research has advocated that plyometric training improves endurance performance. However, a consequence of such a training is the immediate and prolonged appearance of exercise-induced muscle damage (EIMD). This study examined whether a single bout of plyometric exercise, designed to elicit muscle damage, affected cycling endurance performance. Seventeen participants were randomly assigned to either a muscle damage (n = 7 men, 1 woman) or nonmuscle damage (n = 8 men, 1 woman) group. Before and at 48 hours, participants were measured for perceived muscle soreness, peak isokinetic strength, and physiological, metabolic, and perceptual responses during 5-minute submaximal cycling at ventilatory threshold (VT) and a 15-minute time trial. Perceived muscle soreness and isokinetic strength (p < 0.05) were significantly altered in the muscle damage group after EIMD. No changes in heart rate or blood lactate were evident during submaximal exercise (p > 0.05). However, Vo2, V?E, and rating of perceived exertion (RPE) values were increased at VT in the muscle damage group at 48 hours after EIMD (p < 0.05). During the time trial, mean power output, distance covered, and Vo2 were lower in the muscle damage group at 48 hours after EIMD (p < 0.05). However, there was no change in RPE (p > 0.05), suggesting effort perception was unchanged during time-trial performance after EIMD. In conclusion, individuals using concurrent plyometric and endurance training programs to improve endurance performance should be aware of the acute impact of muscle-damaging exercise on subsequent cycling performance.